Tuberculosis of the Central Nervous System Pathogenesis, Imaging, and Management - Turgut, Mehmet; Akhaddar, Ali.; Turgut, Ahmet T.; Garg, Ravindra K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Written and edited by leading international authorities in the field, this book provides an in-depth review of knowledge of tuberculosis of the central nervous system, with emphasis on clinical, diagnostics, and therapeutic features. Tuberculosis, one of the most lethal diseases in human history, still poses a serious threat in the world together with economic and social problems, although a great progress in the fight against this infectious disease in the last century. It covers the full range of tuberculosis of central nervous system and the chapters are organized into six sections: (1) the cranial; (2) the spinal; and (3) the peripheral portions of the nervous system; followed by (4) a section on the laboratory studies in tuberculosis; (5) a section on medical and surgical therapy; and (6) further insights into tuberculosis. This comprehensive reference book will be an ideal source for neurosurgeons, neurologists and specialists upon infectious diseases seeking both basic and more sophisticated information and surgical procedures relating to the complications associated with tuberculosis involving the spine, brain and peripheral nerves.
INTRODUCTION -- SECTION I: GENERAL CONSIDERATIONS -- Historical preview and epidemiology of tuberculosis -- Human genetics of tuberculosis of the nervous system -- Pathogenesis of tuberculosis of the nervous system -- Pathology of tuberculosis of the nervous system (tuberculous meningitis, tuberculoma, tuberculous abscess) -- SECTION II: TUBERCULOSIS OF THE BRAIN AND ITS COVERINGS -- Scalp and the calvarium -- Dura mater and epidural space -- Subdural space -- Cerebrum, cerebellum and deep structures of the brain -- Brainstem -- Ventricles -- Sellar-suprasellar region -- Cavernous sinus -- Vascular complications of tuberculous meningitis -- Imaging findings of tuberculosis of the brain and its coverings -- Surgical therapy -- SECTION III: TUBERCULOSIS OF THE SPINE AND ITS COVERINGS -- Pott$1 (Bs disease -- Spinal dura mater and epidural space -- Spinal subdural space -- Spinal cord -- Imaging findings of tuberculosis of the spine and its coverings -- Surgical therapy -- Video-assisted thoracic surgery for tubercular spondylitis -- SECTION III: TUBERCULOSIS OF THE CRANIAL AND PERIPHERAL NERVES -- Optochiasmatic tuberculosis -- Peripheral neuropathy due to tuberculosis -- Imaging findings of tuberculosis of the cranial and peripheral nerves -- SECTION V: LABORATORY STUDIES IN NEURO-TUBERCULOSIS -- Traditional and new laboratory procedures -- Methods of microbiological confirmation in tuberculous meningitis -- SECTION V: THERAPY OF TUBERCULOSIS OF THE NERVOUS SYSTEM AND ITS COVERINGS -- Medical therapy -- Surgical therapy of tuberculosis of the nervous system and its coverings -- Shunt surgery in childhood tuberculous meningitis with hydrocephalus -- Role of endoscopic third ventriculostomy in tuberculous meningitis with hydrocephalus -- Surgical treatment of thoracic or lumbar spinal tuberculosis complicated with resultant listhesis -- Surgical treatment of spinal tuberculosis complicated with extensive abscess -- Paradoxical worsening of tuberculosis of the nervous system during treatment -- Tuberculosis of the nervous system in immunocompromised hosts -- Management of multidrug-resistant tuberculosis involving the nervous system -- Outcome of tuberculosis of the nervous system and its coverings -- SECTION VI: FURTHER INSIGHTS INTO TUBERCULOSIS -- In vitro and animal models of tuberculosis of the nervous system -- Future research studies -- CONCLUSIONS.s
Keywords: Medicine; Infectious diseases; Neurology; Neurosurgery; Medicine & Public Health; Neurosurgery; Neurology; Infectious diseases